Media in enhancing physical activities : the case study "Dynamic Duo" - Moisio, Terhi (2012)
This Master’s Thesis deals with the potentials of media in enhancing physical activities in the Western postmodern society in the light of a case study Dynamic Duo. Dynamic Duo was a media related campaign in the Finnish national broadcasting company YLE that was targeted in enhancing people’s physical activity. The aim of the thesis is to study in which ways the Dynamic Duo campaign possesses capacity in activating people and, what are the reasons of the participants to take part in the Dynamic Duo campaign. In addition, this thesis investigates what reasons there are in organising campaigns that utilise media in order to increase physical activity. The research data was collected from the participants of Dynamic Duo campaign during 2010 and from the organisation behind the campaign. The participants were Finns of over 35 years of age who took part in the campaign through radio, television and social media. The data was collected with a questionnaire and radio interviews that were found in written forms on the web pages of regional radio stations, as well as through narratives of the participants. The interviews and narratives were examined by using the methods of qualitative analysis supported by quantitative data that was gathered with the questionnaire. Inductive approach and the method of theme analysis together with hermeneutical interpretation were used in the thesis. The analysis shows that there are different reasons to participate the campaigns. The expectations that society places at individuals make people set certain goals. Achieving these goals produces feelings of joy and happiness. Through these so called public challenges people seem to have more motivation as they are under social control during the period of public campaign. The social support tends to be essential in succeeding and reaching the set goals. Also the desire to be model examples in society tempts people to expose themselves as public figures. On the other side, there are also the reasons to organise media related physical activity and health campaigns and the care of public health is the main concern. In organising campaigns that are visible in media there is always two forces colliding, the market forces and entertainment versus common good and non-profit ideology.